Performance Analysis of Hydrokinetic Turbine Using Shroud Ratio Comparison under Yaw Misalignment Condition - Arwizet K; Desmarita Leni; Deviya Aprilman; Adriansyah Adriansyah; Rivanol Chadry (invotek, 2023)
This research aims to analyze the performance of hydrokinetic turbines under yaw misalignment conditions using descriptive statistical methods on coefficient of power (Cp) data. Tests were conducted at water velocities of 0.7, 0.9, and 1.1 m/s for three types of turbine shrouds consisting of turbines without shrouds, turbines with two different types of shrouds, at yaw angles from 0° to 25° with 5° intervals. The study concludes that the performance of each turbine type is significantly influenced by the combination of water flow velocity and yaw angle. The diffuser type has the highest Cp value at every yaw angle, but its performance decreases with increasing yaw angle. The Blade type has poorer performance compared to the diffuser at every yaw angle and has the best performance at a combination of 1.1 m/s velocity and 5° yaw angle. Meanwhile, the shroud type has more stable performance and is not greatly affected by variations in velocity and yaw angle. Based on the analysis of changes in average Cp values with changes in yaw angle at V 0.7 m/s, all three turbine types experienced an increase in Cp value at a yaw angle of 5, with the shroud experiencing the most significant increase. At V 0.9 m/s, the diffuser and shroud types were able to maintain their average Cp values at every yaw angle, while the blade type decreased with increasing yaw angle and experienced a significant decrease at a yaw angle of 25. At V 1.1 m/s, the diffuser and blade types experienced a decrease in performance with every increase in yaw angle, but the shroud type was able to maintain the same Cp value and even experienced a significant increase at a yaw angle of 5.